Structural elucidation of glycosides from the seeds of Entada phaseoloides growing in Thua Thien Hue - Cuong, Le Canh Viet; Lien, Le Thi; Nhi, Nguyen Phuc Khanh; Ha, Tran Phuong; Anh, Le Tuan; Arai, Masayoshi; Anh, Hoang Le Tuan (Vietnam Journal of Science and Technology, 2019)
Entada phaseoloides (L.) Merr. belongs to Fabaceae family and widely distributes throughout Vietnam, Thailand, Malaysia, Indonesia, Philippines, China, New Guinea, and Australia. In Vietnamese traditional medicine, the seeds of Entada phaseoloides were used for the treatment of stomachache, haemorrhoids, and hernia diseases. In this article, we report the isolation and structural elucidation of four glycosides from the water extract of seeds of E. phaseoloides including phaseoloideside C (1), phaseoloideside E (2), acanthoside D (3), and 1-(3,4,5-trimethoxyphenyl)prop-7-en-9-ol-O-(6ʹʹ-O-α-L-arabinopyranosyl)-β-D-glucopyranoside (4). To the best of our knowledge, compounds 3-4 were isolated from E. phaseoloides for the first time